2023
DOI: 10.1563/aaid-joi-d-22-00053
|View full text |Cite
|
Sign up to set email alerts
|

Guided Lateral Window Osteotomy Using Dynamic Navigation for Maxillary Sinus Augmentation: A Novel Technique

Abstract: No abstract is required for case letters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Studies have indicated that the accuracy of DN is similar to that of a static guide in assisting implant placement [ 17 19 ], and both of which are better than that of the free hand [ 20 23 ]. Currently, few reports about the application of DN in MSFE have been found after a throughout search [ 24 , 25 ]. Wu et al reported the application of DN in the surgery of TSFE [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have indicated that the accuracy of DN is similar to that of a static guide in assisting implant placement [ 17 19 ], and both of which are better than that of the free hand [ 20 23 ]. Currently, few reports about the application of DN in MSFE have been found after a throughout search [ 24 , 25 ]. Wu et al reported the application of DN in the surgery of TSFE [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al reported the application of DN in the surgery of TSFE [ 24 ]. Bishbish et al conducted a pilot application of DN in LWSFE [ 25 ]. Bone grafts applied during MSFE, especially in LWSFE, however, whether they would affect the accuracy of implant placement under DN has not been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maxillary sinus is lined by a membrane called the Schneiderian membrane. This membrane is extremely thin, averaging 0.4 mm to 1.5 mm in most individuals [ 17 , 18 ]. Furthermore, several anatomic anomalies can further complicate a sinus lift procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of sinus membrane rupture during a direct sinus lift can vary depending on several factors, including the sinus's anatomy, the surgeon's experience and skill, and the technique used. Proper preoperative assessment, including radiographic imaging such as CBCT, can help evaluate the thickness and integrity of the sinus membrane and aid in treatment planning [ 17 , 18 , 20 ].…”
Section: Discussionmentioning
confidence: 99%